The Influence of Organizational Transformation and Employee Engagement on Employee Performance at PT Dayamitra Telekomunikasi Tbk. - aji prabowo, wicky; Wahyuningtyas, Ratri (International Journal Labs, 2025)
This study aims to examine organizational transformation, employee engagement, and employee performance at PT Dayamitra Telekomunikasi Tbk (Mitratel). Additionally, it investigates the influence of organizational transformation and employee engagement on employee performance. The research adopts a quantitative approach using questionnaires and literature reviews for data collection. Probability sampling was applied, involving 206 permanent employees from a total population of 424, representing five company directorates. Data analysis was conducted using Structural Equation Modeling (SEM) - Partial Least Square (PLS). Organizational transformation at Mitratel achieved positive results with an average score of 861.89 (83.68%), reflecting optimism towards new strategies that foster growth and opportunities. Employee engagement recorded a very high average score of 865.78 (84.06%), indicating strong motivation and dedication. While employee engagement significantly influences employee performance, organizational transformation shows no significant impact on employee performance. The study provides insights into the distinct impacts of organizational transformation and employee engagement on employee performance, highlighting the critical role of employee engagement in driving organizational competitiveness.